CORRELATION BETWEEN STRUCTURAL RETINAL NERVE FIBRE LAYER THICKNESS AND FUNCTIONAL VISUAL FIELD LOSS IN PRIMARY OPEN ANGLE GLAUCOMA - Arun, A.; A., Sadhana; Dudala, Shankar Reddy (BALI MEDICAL JOURNAL; Vol 4 No 1 (2015), 2015)
Background: Glaucoma is characterized by progressive degeneration of retinal ganglion cells and their axons that leads to nerve fiber layer loss, optic disc cupping, and consecutive glaucomatous visual field changes. Study is done in Department of ophthalmology, S.V.R.R Government General Hospital, S.V.Medical College Tirupati. A total of 52 eyes of 29 patients were included in the study. Mean age of the patients included in the study is 64.14+/- 11.43 years. Majority were male patients (68.96%). Female patients were only 31.04%.
Keywords: Retinal, Nerve, Fibre, Primary, Open, Angle Glaucoma